2018
DOI: 10.1093/schbul/sby093
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Variants Shared Between Smoking Quantity and Schizophrenia on 15q25 Are Associated With CHRNA5 Expression in the Brain

Abstract: Cigarette smokers with schizophrenia consume more cigarettes than smokers in the general population. Schizophrenia and smoking quantity may have shared genetic liability. Genome-wide association studies (GWASs) of schizophrenia and smoking quantity have highlighted a biological pleiotropy in which a robust 15q25 locus affects both traits. To identify the genetic variants shared between these traits on 15q25, we used summary statistics from large-scale GWAS meta-analyses of schizophrenia in the Psychiatric Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…It is further feasible that single genetic markers for schizophrenia, bipolar disorders, major depression, and intelligence of large effect, rather than an aggerate of common genetic markers of small effect, in uences the risk of smoking initiations in the general population. For example, one of the robust schizophrenia associated loci identi ed by a large genome-wide association study meta-analysis [17] has been found in a gene cluster encoding neuronal nicotinic acetylcholine receptors (nAChR), which is linked to heaviness of smoking in the general population [10,39]. However, by design, polygenic scores do not capture other structural variants beyond common genetic markers of relatively small effects, such as rare variants, poorly tagged or multiple independent variants, gene-by-gene interactions and gene-environment correlations [40].…”
Section: Discussionmentioning
confidence: 99%
“…It is further feasible that single genetic markers for schizophrenia, bipolar disorders, major depression, and intelligence of large effect, rather than an aggerate of common genetic markers of small effect, in uences the risk of smoking initiations in the general population. For example, one of the robust schizophrenia associated loci identi ed by a large genome-wide association study meta-analysis [17] has been found in a gene cluster encoding neuronal nicotinic acetylcholine receptors (nAChR), which is linked to heaviness of smoking in the general population [10,39]. However, by design, polygenic scores do not capture other structural variants beyond common genetic markers of relatively small effects, such as rare variants, poorly tagged or multiple independent variants, gene-by-gene interactions and gene-environment correlations [40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genome‐wide association studies (GWAS) revealed that the CHRNA5–CHRNA3–CHRNB4 cluster on chromosome 15, coding for neuronal nicotinic acetylcholine receptor subunits, is associated with schizophrenia and different smoking traits 9–13 . Consequently, the reason for the high prevalence of smoking in SzP is currently under debate, and the consideration of tobacco as a risk factor for schizophrenia is becoming strongly supported 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Interestingly, genome-wide association studies (GWAS) revealed that the CHRNA5-CHRNA3-CHRNB4 cluster on chromosome 15, coding for neuronal nicotinic acetylcholine receptor subunits, is associated with schizophrenia and different smoking traits. [9][10][11][12][13] Consequently, the reason for the high prevalence of smoking in SzP is currently under debate, and the consideration of tobacco as a risk factor for schizophrenia is becoming strongly supported. [14][15][16] Mendelian randomization (MR) studies, which use genetic variants associated with the risk factor of interest as instrumental variables to assess causality, are an alternative to observational studies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, among the GWASs of smoking-related phenotypes from the TAG, only an association between a genomic locus on 15q25 and smoking quantity has been revealed in smoking GWASs 16 . We found that genome-wide significant single-nucleotide polymorphisms (SNPs) on 15q25 shared between schizophrenia and smoking quantity contributed to a common pathophysiology underlying these phenotypes via altered CHRNA5 expression in the brain 23 .…”
Section: Introductionmentioning
confidence: 99%